A successful use of systems approaches in cross‐disciplinary healthcare improvement. Issue 1 (16th August 2018) - Johnson, Julian; Smith, Gary; Beck, Fran; Harding, Alan
Abstract: UK Healthcare is facing many different trends: a changing demographic of an ageing and 'frail' population; increasing numbers of the population living with at least two long term conditions; improvements in medical care and interventions which can treat a larger number of conditions; continued budget pressures and raising expectations. Healthcare is a complex socio‐technical system, and to identify and devise interventions with clear net benefits is a challenge: we see a classic 'wicked problem'. The outcome from three INCOSE‐facilitated multi‐disciplinary workshops was a coherent prioritised work programme, with buy‐in from all stakeholders, and traceable back to original issues and opportunities. This presentation will explain the context, the engagement from INCOSE, the nature of the workshops and techniques applied, and the outcomes. The developed programme supports the Shropshire and Telford NHS Sustainability and Transformation Plan (STP). Arguably the biggest ongoing challenge remains handling complexity and coherence across multiple stakeholder perspectives.